“Shop Until You Drop”: Valuing Fentanyl Analogs on a Swedish Internet Forum - Møller, Kim (Journal of drug issues, 2021)
Fentanyl analogs are synthetic opioids used for pain treatment and palliative care, which are also sought after by drug users for their psychoactive properties. Clandestinely produced fentanyl has caused an overdose crises of unprecedented scale in the United States. In Sweden, the retail purchase, possession, and use of some analogs are legal, providing opiate users with a legal alternative, until the process of scheduling is finished. The continuous process of scheduling and introduction of slightly modified variants implies that there is much uncertainty regarding the potency and quality of newly introduced analogs. We examine user perceptions of fentanyl analogs in a thematic analysis of the public internet forum, Flashback, from 2012 to 2019. In 24 threads on fentanyl analogs, posters shared and discussed information on the emergence of new analogs, their desirability and prices, adverse health effects, and eventual scheduling.